Non-Traditional Security Paradigm and Role of Intelligence: Challenges of Transformation - Muhammad Ajmal Abbasi, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
The triumphant elation of neo-liberal global order against the Marxist challenge after the cold war was soon replaced by a somber recognition that the world is still far from being a peaceful place. Post-cold war international environments had started revamping the global political order where the traditional notion of territorial security has been getting increasingly irrelevant. While conflicts in kinetic domain are persistent in some form, the broader concept of security highlights gravity of constantly evolving non-traditional threats. This emerging challenge, primarily categorized among the non-military threats, has caused a functional dilemma for the national security apparatus. Apparently, National Intelligence Community (NIC) is the most viable mechanism to anticipate, identify and forecast the non-traditional security threats. However, without undertaking necessary reforms, conventionally trained and organized NIC seems least prepared for the evolving challenges. It is, therefore, imperative that the intelligence agencies are adequately transformed and structured for the impending task.